Summertime photochemistry during CAREBeijing-2007: ROx budgets and O3 formation - F. Costabile; A. Amoroso; L. Zeng; M. Shao; T. Zhu; J. Liao; R. Stickel; L. G. Huey; C. Zhao; D. Gu; Y. Wang; Z. Liu; et al. (Atmospheric Chemistry and Physics, 2012)
We analyze summertime photochemistry near the surface in Beijing, China, using a 1-D photochemical model (Regional chEmical and trAnsport Model, REAM-1D) constrained by in situ observations, focusing on the budgets of ROx (OH + HO2 + RO2) radicals and O3 formation. While the modeling analysis focuses on near-surface photochemical budgets, the implications for the budget of O3 in the planetary boundary layer are also discussed. In terms of daytime average, the total ROx primary production rate near the surface in Beijing is 6.6 ppbv per hour (ppbv h−1, among the highest found in urban atmospheres. The largest primary ROx source in Beijing is photolysis of oxygenated volatile organic compounds (OVOCs), which produces HO2 and RO2 at 2.5 ppbv h−1 and 1.7 ppbv h−1, respectively. Photolysis of excess HONO from an unknown heterogeneous source is the predominant primary OH source at 2.2 ppbv h−1, much larger than that of O1D+H2O (0.4 ppbv h−1). The largest ROx sink is via OH + NO2 reaction (1.6 ppbv h−1), followed by formation of RO2NO2 (1.0 ppbv h−1) and RONO2 (0.7 ppbv h−1). Due to the large aerosol surface area, aerosol uptake of HO2 appears to be another important radical sink, although the estimate of its magnitude is highly variable depending on the uptake coefficient value used. The daytime average O3 production and loss rates near the surface are 32 ppbv h−1 and 6.2 ppbv h−1, respectively. Assuming NO2 to be the source of excess HONO, the NO2 to HONO transformation leads to considerable O3 loss and reduction of its lifetime. Our observation-constrained modeling analysis suggests that oxidation of VOCs (especially aromatics) and heterogeneous reactions (e.g. HONO formation and aerosol uptake HO2) play potentially critical roles in the primary radical budget and O3 formation in Beijing. One important ramification is that O3 production is neither NOx nor VOC limited, but in a transition regime where reduction of either NOx or VOCs could result in reduction of O3 production. The transition regime implies more flexibility in the O3 control strategies than a binary system of either NOx or VOC limited regime. The co-benefit of concurrent reduction of both NOx and VOCs in reducing column O3 production integrated in the planetary boundary layer is significant. Further research on the spatial extent of the transition regime over the polluted eastern China is critically important for controlling regional O3 pollution.